Cost utility analysis of endoscopic sinus surgery for chronic rhinosinusitis with and without nasal polyposis. (21st July 2016) - Scangas, George A.; Remenschneider, Aaron K.; Su, Brooke M.; Shrime, Mark G.; Metson, Ralph
Abstract : Objective: To evaluate the cost‐effectiveness of endoscopic sinus surgery (ESS) compared to medical therapy for patients with chronic rhinosinusitis (CRS) with and without nasal polyposis (NP). Study Design: Cohort‐style Markov decision‐tree economic model with a 36‐year time horizon. Methods: Two cohorts of 229 CRS patients with and without NP who underwent ESS were compared with a matched cohort of 229 CRS patients from the Medical Expenditures Survey Panel database (Agency for Healthcare Research and Quality, Rockville, MD) who underwent medical management. Utility scores were calculated from sequential patient responses to the EuroQol five‐dimensions questionnaire. Decision‐tree analysis and a 10‐state Markov model utilized published event probabilities and primary data to calculate long‐term costs and utility. The primary outcome was the incremental cost per quality‐adjusted life year (QALY). Thorough sensitivity analyses were performed. Results: The reference case for CRS with NP yielded an incremental cost‐effectiveness ratio (ICER) for ESS versus medical therapy of 5, 687.41/QALY. The reference case for CRS without NP yielded an ICER of 5, 405.44/QALY. The cost‐effectiveness acceptability curve in both cases demonstrated 95% certainty that the ESS strategy was the most cost‐effective option at a willingness‐to‐pay threshold of 20, 000/QALY or higher. These results were robust to one‐way and probabilistic sensitivity analysis. Conclusion: This study demonstrates the cost‐effectiveness of ESS compared to medical therapy alone for the management of CRS patients both with and without NP. The presence of nasal polyps was not found to affect the overall cost‐effectiveness of ESS. Level of Evidence: 2C. Laryngoscope, 127:29–37, 2017